Language Interference of Batak Angkola-Mandailing Language to Indonesian: A Case Study - Lita Rizki Fauziah (Passage, 2015)
This research aims to investigate the common characteristics of Indonesian pronunciation deviations made by undergraduate college students from Batak Angkola and to observe the factors that contribute to the interference. The participants are two female Batak Angkola undergraduate students who have been living in Bandung for four years and are active speakers of Bahasa Indonesia and Batak Angkola-Mandailing language. To compare the results, four other participants who come from Jakarta and Bandung, have the same age and gender, and are not active speakers of any Indonesian local languages are also recruited. Based on the pilot test conducted prior to the research, the phonemes that are investigated are /e/, /ə/ and plosives (/b/, /d/, /g/, /k/, /t/, /p/). The data are collected through two types of assessment, which are a reading task, and pronunciation tests in the form of three word lists. By using software Praat, the deviations analysis and a further acoustic phonetic analysis of vowel and consonant duration are conducted. In general, there are two types of pronunciations deviations made by the participants: devoicing and allophonic shift that occurs between /ə/ into /e/ and /e/ into /ə/. The factors that contribute to the interference are speaker bilingualism background, language distant, anxiety, empathy and group solidarity.Keywords: Language interference, pronunciations, acoustic phonetics, Batak Angkola-Mandailing language.